Antiulcerogenic activity of four extracts obtained from the bark wood of Quassia amara L. (Simaroubaceae) - Toma, W.; Gracioso, J. D.; de Andrade, FDP; Hiruma-Lima, C. A.; Vilegas, Wagner [UNESP]; Brito, ARMS (Pharmaceutical Soc Japan, 2002)
Quassia amara L., a neotropical forest shrub of the Simaroubaceae family, is widely used in Caribbean folk medicine and in some northern states of Brazil for the treatment of gastric ulcers. This plant is a source of numerous compounds including both beta-carbonile and cantin-6 alkaloids as well as, primarily, the bitter compounds known as quassinoids. We analyzed the possible antiulcerogenic activities of four extracts of different polarities: 70% ethanol (70% EtOH), 100% EtOH, 100% dichloromethane (DCM), and 100% hexane (HEX) obtained from Quassia amara bark. All extracts, administered at doses of 5000 mg/kg orally and 1000 mg/kg intraperitoneally, caused neither toxicity or death. In the indomethacin[bethanechol-induced gastric ulcer, 70% EtOH, 100% EtOH, DCM and HEX extracts, 100 mg/kg, p.o., inhibited the gastric ulcer (22.5, 23.4, 50.5, 46.8%, respectively). 70% EtOH, 100% EtOH, DCM, and HEX extracts reduced the gastric injury induced by the hypothermic restraint-stress test in mice (70.7, 80, 60, 82.7%, respectively). In the pylorus ligature of the mouse stomach, following pre-treatment with a single intraduodenal administration of 100 mg/kg of each extract, only 70% EtOH did not change the biochemical parameters of gastric juice. 100% EtOH, DCM and HEX extracts presented decreased gastric juice content, increased pH values and decreased acid output. We also determined the antiulcerogenic activity on HCl-EtOH-induced gastric ulcers in mice at four doses (25, 50, 75, 100 mg/kg, p.o.), then evaluated the possible dose-dependent relation and calculated the ED50 values. Except for 70% EtOH at a dose of 25 mg/kg, the other extracts showed significantly activity (p<0.05). The free mucous amount in the gastric stomach content was also evaluated. All extracts showed significant increases (p<0.05) of free mucous. This effect was abolished when the animals were pre-treated with indomethacin. Prostaglandin synthesis was evaluated by the administration of HEX extracts by the oral route (100 mg/kg). Prostaglandin synthesis was significantly, increased by 52.3% (p<0.05), and this effect was abolished with prior administration of indomethacin. We concluded that Quassia amara is a probable source for a new drug to treat gastric ulcers, and the mechanism of its activity relates to cytoprotective factors, such as mucous and prostaglandins, but there is still the possibility that antisecretory activity is involved in its antiulcerogenic effect.
Keywords: Quassia amara; phytochemical analysis; antiulcerogenic activity